2020
DOI: 10.1007/s11269-020-02524-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Links Among Poverty, Hydroenergy and Water Use Using Data Mining Methods

Abstract: Water is fundamental to human well-being, social development and the environment. Water development, particularly hydropower, provides an important source of renewable energy. Water development is strongly affected by poverty, but only few attempts have been made to understand the links between water development and poverty from a global water development point of view. In this work, this linkage was explored using reservoir construction, hydroenergy and water use data along with six derived indicators. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Water resources are the lifeblood for regional development and human survival (Tian et al, 2020). The rational utilization and development of water resources support and guarantee the sustainable growth of the regional economy, which has become a national concern and focus (Roozbahani et al, 2015).…”
Section: Further Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Water resources are the lifeblood for regional development and human survival (Tian et al, 2020). The rational utilization and development of water resources support and guarantee the sustainable growth of the regional economy, which has become a national concern and focus (Roozbahani et al, 2015).…”
Section: Further Discussionmentioning
confidence: 99%
“…Increased investment in other resources will drive regional economic growth (He et al, 2020), play a certain role in improving the utilization efficiency of water resources, and increase scale efficiency. With the expansion of the production scale, such scale benefits become increasingly obvious, improving the utilization rate of water resources (Tian et al, 2020).…”
Section: Further Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "waterscapes" influence on the administrative geography of the region, which were the locations where these activities took place, and the people in charge of them were integrated within the socio-economic network [14]. Water development, particularly hydropower, provides an important source of renewable energy [15]. Water Engineering Modelling and Mathematic Tools provides an informative resource for practitioners who want to learn more about different techniques and models in water engineering and their practical applications and case studies [16].…”
Section: Introductionmentioning
confidence: 99%
“…MTGAvailable resources per capita represent the level of resources available in a region. In addition, Recent studies have found a strong linkage between water and poverty(Tian et al 2020). Cultivated land area, grassland area, and river density were used to consider the in uence of local agricultural production patterns on poverty.…”
mentioning
confidence: 99%